La Chiesa della Tabula Ansata a Umm al-Rasas – Kastron Mefaa - Piccirillo, M. (Liber Annuus, 2003)
Abstract The small church, which we later named “of the Priest Waʼil”, was among the first sacred Christian edifices identified among the ruins of Umm al-Rasas by explorers. On closer examination of the ruins on the south-western edge of the area beyond the walls of the castrum, we realized that the small church was part of an ecclesiastical complex comprising, to the south east, a larger church partly hidden by a modern house built by a family of the Salyata Bedouins. The main edifice, which we named the “Church of the Tabula Ansata”, from an inscription in Greek framed in a tabula incised on a stone slab of the presbytery, was built in the 6th century and has been restored in the first half of the 7th century. In the first phase, the church was paved with mosaics, which were later covered by stone slabs on an upper level in the presbytery and transferred to the nave. Traces of the original mosaic floor in the nave below the stone slabs of the upper floor and the stone elements of an arch fallen in a north south direction leads us to the hypothesis that the sacred area originally reserved for the liturgical celebration was limited to the eastern sector of the church.